Barriers to Effective Implementation of Inclusive Education Curriculum in Selected Public Primary Schools in Temeke Municipality - Jamila H. Nuru; Michaela Mhagama; Frank Mwamakula (PT. Pusmedia Group Indonesia, 2025)
Despite national and global policy frameworks, including Tanzania's Education and Training Policy (2014), the implementation of inclusive education remains constrained in resource-limited contexts. This study explored the challenges of implementing inclusive education in public primary schools in Temeke Municipality, Tanzania. Using a mixed-methods descriptive design, data were collected from 111 participants, including teachers, students, head teachers, and parents, through questionnaires, interviews, and document review. Findings reveal a significant gap between policy and practice, driven largely by limited teacher capacity, with over 55 per cent lacking formal training in inclusive education and half reporting inadequate preparedness for inclusive teaching. These challenges are compounded by shortages of teaching and learning resources, inconsistent application of inclusive strategies, and the absence of structured support systems. The study concludes that systemic barriers including insufficient professional development, inadequate resources, and weak support structures hinder effective implementation of inclusive education. It recommends mandatory and continuous teacher training, increased investment in adapted materials and infrastructure, establishment of collaborative support mechanisms, and strengthened monitoring and evaluation frameworks to promote equitable and quality education for all learners.